Differing Teaching Formats: Pre-Service Teachers' Professional Competency Development in Linguistically Responsive Teaching - Hammer Svenja; Berkel-Otto Lisa (De Gruyter, 2019)
Teaching multilingual learners in content classrooms is still a challenge for most teachers due to the fact that teacher education is still lacking consistent concepts in this area. Hence, opportunities to learn in teacher education programs need to be examined with regard to content, structure and format. This study deals with the question whether the competencies needed to teach multilingual learners are actually learnable through opportunities to learn in university classes. Three different class formats were examined: 100% online via an e-learning platform, 100% face-to-face, and a blended learning version (50% online, 50% face-to-face). The learning outcome was measured in a pre-post-design on the basis of the level of competency concerning teaching multilingual learners (DaZKom). First results indicate that the competencies to teach multilingual learners increase through the opportunities to learn we offered. Furthermore, the study shows that all three class formats resulted in an increase in competency. The study reaches the conclusion that further opportunities to learn are needed for teachers to be adequately prepared to facilitate multilingual learners in content classrooms.